2022
DOI: 10.1039/d2na00160h
|View full text |Cite
|
Sign up to set email alerts
|

Flow-induced-crystallization: tailoring host–guest supramolecular co-assemblies at the liquid–solid interface

Abstract: Here, we report that using the method of simply contacting the sample solution droplet with a piece of tissue paper can create a solvent flow (capillary force). During this process,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…In other words, the planar guest molecules help to maintain the bilayer template via host–guest van der Waals interaction, which has not been reported thus far to our knowledge. For a parallel test, the use of fullerene (e.g., C 60 ) failed to obtain the Kagomés although such a three-dimensional (3D) guest promoted bilayer formations of TPTC at the liquid–solid interface. , For saturated or a higher concentration condition (5.0 × 10 –4 M) of BPTC, coexisting phase separations of the bilayer Kagomé and BPTC domains were found frequently (Figure S8). Furthermore, it has been reported in the literature that COR dimers (bilayers) hardly form even in a cavity .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, the planar guest molecules help to maintain the bilayer template via host–guest van der Waals interaction, which has not been reported thus far to our knowledge. For a parallel test, the use of fullerene (e.g., C 60 ) failed to obtain the Kagomés although such a three-dimensional (3D) guest promoted bilayer formations of TPTC at the liquid–solid interface. , For saturated or a higher concentration condition (5.0 × 10 –4 M) of BPTC, coexisting phase separations of the bilayer Kagomé and BPTC domains were found frequently (Figure S8). Furthermore, it has been reported in the literature that COR dimers (bilayers) hardly form even in a cavity .…”
Section: Resultsmentioning
confidence: 99%
“…Either flexible or robust molecular networks can allow the formation of co-crystals upon guest molecule incorporation. While multicomponent co-crystal systems have been reported, , examples of layered molecular structures involving more than one molecular building block are rare. …”
Section: Introductionmentioning
confidence: 99%
“…De Feyter et al , and Lee et al have demonstrated that solution flow direction could affect the adlayer assembly, structure, and stability. However, effects due to the direction of solution flow with respect to the substrate were not observed during these experiments.…”
Section: Resultsmentioning
confidence: 99%
“…(2) large scan areas should be imaged, and (3) regions surrounding the area of interest must be imaged to confirm uniform growth. De Feyter et al 58,59 and Lee et al 60 have demonstrated that solution flow direction could affect the adlayer assembly, structure, and stability. However, effects due to the direction of solution flow with respect to the substrate were not observed during these experiments.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Often, the addition of guest molecules to the host network (host-guest co-assembly) is investigated either on the solid surface or in solution. 83,84 Each of these has its unique advantages. 85 The specific interactions between the host and guest take place over atomic dimensions.…”
Section: Synergistic Effect Of Chemical Stimulimentioning
confidence: 99%